Using intraverbal training to increase symbolic play in children with autism spectrum disorder. (6th July 2020) - Lee, Gabrielle; LeePark, Hyesuk; Kim, Seungju; Park, Mi‐seong; Park, Soohyun
Abstract : We evaluated the effects of an intraverbal training procedure on the acquisition, maintenance, and generalization of object‐substitution symbolic play in three 6‐year‐old Korean boys with autism spectrum disorder. A multiple probe across four behaviors design was used. All children acquired target symbolic play behavior, and novel responses emerged in training and follow‐up conditions. Generalization of object substitutions to untaught objects occurred in all three children. Free play observations indicated that symbolic play emerged in one child, and functional play increased in all three children.